Penning trap mass spectrometry of radionuclides - Kluge, Heinz-Jürgen (International journal of mass spectrometry, 2013)
Trapping and cooling techniques play an increasingly important role in many areas of science. This publication focuses on high-accuracy mass spectrometry of radionuclides by use of Penning traps where storing and cooling is also essential. The pioneering set-up, the very first Penning trap installed at a radioactive-beam facility was ISOLTRAP, still in operation after almost thirty years at the on-line isotope separator ISOLDE at CERN. This publication describes how ISOLTRAP was developed over the years as a high-performance mass spectrometer. In the meantime, the application of Penning traps to mass spectrometry of short-lived nuclei became very popular so that such systems are operated or planned at nearly all radioactivebeam facilities worldwide.
Gesehen am 08.06.2022